Expressão de microRNAs cardíacos induzida por treinamento físico durante insuficiência cardíaca - Cunha, João Paulo Queiroz Cardoso da [UNESP] (2013)
MicroRNAs (miRNAs) are a class of small noncoding RNAs that have gained status as important regulators of post-transcriptional gene expression during development and in certain diseases such as heart failure (HF). Although there is no consensus that adjuvant therapies for cardiovascular disease are able to increase patients' quality of life and survival rates a non-pharmacological therapy, exercise training (ET) can reduces a number of cardiovascular risk factors and has been recognized as an important and safe strategy for preventing and treating heart failure. Therefore, we evaluate the effects of ET prescribed during the transition from cardiac hypertrophy to heart failure on cardiac micro-RNA profile. We employed ascending aortic stenosis (AS) to induce heart failure in Wistar male rats (n=10) by a stainless-steel clip. Sham-operated animals (n=5) were used as controls. Eighteen weeks after surgery, when AS animals presented ventricular dysfunction, detected by echocardiogram, rats were randomized to 10 weeks of supervised exercise training (HF-ET, n=5) or to a control sedentary group (HF-S, n=5). At the end of the experiment, heart failure was evaluated by clinical data and the cardiac remodeling by morphologic and functional data obtained by echocardiogram. The expression levels of 373 miRNAs from left ventricles were measured by real-time quantitative PCR using TaqMan Rodent microRNA Array (cards A + B) on an ABI ViiA7 Sequence Detection System and the mean relative quantity (RQ) was calculated and miRNAs differentially expressed between groups were defined as those with >1.5-fold change and P<0.05 (two sample, two tailed Student’s t-test). At the end of the experiment (28th wks), exercise training attenuated the clinical and pathological signs of HF. It also attenuated cardiac remodeling with maintenance of systolic and diastolic function. Moreover, miRNAs analysis revealed that thirty-five ...